Analyse des strategies argumentatives : Etude comparee des discours Sarkozy - Hollande (Journal of the College of Languages (JCL), 2014)
The argumentation find its origins in some conceptions laid by Aristote. A speaker always intends to influence his hearers to change their beliefs. Therefore, this study deals with texts of the political speech of the French presidents Nicolas Sarkozy and François Hollande in the treatment of argumentative strategies.